Інкорпорація документального ресурсу в сучасній художній літературі - Поліщук, Я. (Слово і Час, 2018)
У статті досліджено вплив документального начала на модифікації сучасної художньої
літератури. Автор фіксує цю тенденцію як прикметну для нашого часу. Спираючись на праці
теоретиків літератури, він пропонує арбітральний критерій досвіду в оцінці змішаних літературних
форм. Заявлена проблема аналізується на прикладі воєнного тексту сучасної української
літератури, зокрема романів Є. Положія “Іловайськ” (2015), О. Іванюк “Амор[т]е” (2017) та
В. Рафєєнка “Довгі часи” (2017). У тематичному плані ці твори містять чимало паралелей,
адже в них зображуються різні аспекти війни на Донбасі 2014 – 2018 рр. Зате на рівні поетики
проявляються відмінні стратегії організації тексту – від прямого включення документа в авторську
оповідь до його фрагментаризації, реорганізації та адаптації (залежно від інтенції автора та
особливостей задуму твору). The influence of the documentary background on the modifications of contemporary literature is the
main subject of the research, presented in this article. The author shows this process as a contemporary
tendency. Appealing to the prominent theoretical works he suggests an arbitral criterion of experience
for the evaluation of mixed literary forms. The analysis of the main problem of the research is based
on the war texts of the contemporary Ukrainian literature. Among them are such novels as “Ilovaysk”
(2015) by Serhiy Polozhiy, “Amor[t]e” (2017) by Oleksandra Ivaniuk and “Long Time” (“Dovhi Chasy”,
2017) by Volodymyr Rafayenko. Despite related themes in these texts, they reveal different aspects
of the war in Donbas. The novels have absolutely different strategies of forming composition: from
the direct inclusion of the document in the author’s narrative to its fragmentation, reorganization, and
adaptation, depending on the author's intention and the design intent of the work. Incorporation of
documentary texts into the narrative of fiction is a widespread and successful process of actualizing
literature, approaching it to a public inquiry. This postulates a significant potential for the development
of literature as an aesthetic proposal and a cultural institution. In the presented works about the war
the documentary element had a very significant impact. Due to it, the war is depicted in its humanistic
dimension. There is a special type of a hero, committed and motivated, but not idealized. Blending
styles and discourses has also been a productive experience. Thus the literature prompts rethinking
of the concept of war in public opinion. В статье исследуется влияние документального
начала на модификации современной литературы. Автор
фиксирует эту тенденцию как характерную для нашего
времени. Опираясь на труды теоретиков литературы, он
предлагает арбитральный критерий опыта для оценки
смешанных литературных форм. Заявленная проблема
анализируется на примере военного текста современной
украинской литературы, в частности романов Е. Положия
“Иловайск” (2015), А. Иванюк “Амор[т]е” (2017) и
В. Рафеенко “Долгота дней” (2017). В тематическом плане
эти произведения обнаруживают немало параллелей, так как в них изображены различные аспекты войны
на Донбассе 2014 – 2018 гг. Зато на уровне поэтики проявляются различные стратегии организации текста –
от прямого включения документа в нарратив автора до его фрагментаризации, реорганизации и адаптации (в
зависимости от интенции автора и особенностей замысла произведения).